Purification and Characterization of Carboxymethyl Cellulase By A Catabolite Repression Resistant Mutant Strain of Pseudomonas Sp. (Psccrrnt9) - B. Sreedevi; D. Madhusudan Reddy; N Kishore (International Journal of Pharma and Bio Sciences, 2022)
Cellulose degrading organisms are being employed for the conversion of native cellulosic materials into soluble sugars. Cellulases are commercially important enzymes and have applications in various eco-friendly processes. For enhanced cellulase production, a high priority has been given to several approaches including chemical mutations, UV irradiations and genetic engineering. Genetically improved strains have been employed in a number of applications including animal feed, pharmaceutical and textile industries. Cellulolytic microorganisms in their typical habitat in nature probably depend on the phenomenon of catabolite repression and act as a control on cellulase synthesis. Cellulase biosynthesis severely limits the ability of wild type cultures to produce cellulase on a commercial scale and hampers its application in the biomass conversion process. Various methods have been developed to obtain catabolite repression resistant mutants. The potential industrial utilization of cellulose will require organisms that have high cellulase activity and are no longer under repressive control. Purified cellulases from improved mutants that exhibit high temperature stability, activity over a wide range of pH under non-conventional conditions are of great interest and are employed in a variety of industrial applications. In the present investigations, Carboxymethyl cellulase (CMCase) of a catabolite repression resistant mutant strain of Pseudomonas (PsCCRRNT9) when subjected to partial purification by (NH4)2SO4 precipitation, a 15.65-fold purification was observed and was later on characterized. Two protein bands with molecular weights 53.0 and 85.1 were detected during SDS-PAGE analysis. Further investigations revealed that the CMCase from this strain is active over a wide range of pH (6-10) and exhibited maximum activity at temperature 50 0C. Of different metal ions investigated, CaCl2.2H2O was found to enhance the CMCase activity at 5 mM and 10 mM concentrations. CMCase activity was completely inhibited at 10 mM concentration of HgCl2.